(untitled) (Research, Society and Development, 2021)
Atrazine is a herbicide widely used in control of predominant broad leaf infestations in agricultural crops such as corn, sorgo and sugarcane, with high mobility in the soil, and may become toxic to aquatic organisms, plants and humans. Thus, the adsorption of pesticides by biocoals becomes a viable option, mitigating the environmental impacts caused. Used in physico-mathematical models, ion leaching tests in soil column, allow the characterization of the mobility of solutes presenting differential equation solutions for transportof solutes in the soil. Thus, the present study aims to verify the adsorption potential of atrazine by biochar synthesized from corn straw in an undefined and deformed soil column. For this, the experiment was conducted in a completely randomized design, totaling 16 tests (deformed column with biochar, deformed column without biochar, undisturbed column with biochar and undisturbed column without biochar). The treatments with bio-carbon received an amount of 5 ton ha-1 and all received the same amount of atrazine (6,5 L ha-1). The biochar was characterized based on their physical and chemical properties, by surface morphology evaluation (Scanning Electron Microscopy - SEM), specific surface area and porosity. Atrazine concentrations were measured by High Performance Liquid Chromatography (HPLC). In the undisturbed soil, it was found that significant differences in adsorption of atrazine after application of the biochar, once reduced pesticide mobility in soil. However, the method used in soil column deformed was not efficient, making necessary more studies to this perspective.